Teaching in a Cold and Windy Place : Change in an Inuit School - Tompkins, Joanne, 1956- (Book collections on Project MUSE., 1998)
Joanne Tompkins travelled to the Baffin Island community of Anurapaqtuq to take on the job of principal at the local school. This is the fascinating story of her experiences in the four years she spent there and the many challenges she faced.On her arrival in the Inuit village, Tompkins found struggling teachers and failing students in a community that was grappling with social and economic change. Outlining strategies that worked and others that failed, she gives a vivid account of the day-to-day trials and rewards that she and community members experienced as they worked to create a productive and exciting school environment.This engaging and informative account of change in an Inuit school will be of great use to educators and administrators, and appeal to general readers as well. One educator who read the manuscript paid it the compliment of comparing it to Sylvia Ashton-Warner's classic tale of teaching Maori children, Teacher.